1976
DOI: 10.1136/jcp.29.11.1007
|View full text |Cite
|
Sign up to set email alerts
|

Indirect immunofluorescence assay for antibody to germ tube of Candida albicans--a new diagnostic test.

Abstract: Indirect immunofluorescent and agglutination assay were used to study the anti-Candida albicans reactivities in the serum of 13 normal subjects and 14 patients infected with C. albicans. A significant increase in anti-C. albicans seroreactivity was observed during infection with this organism but the increase in the anti-germ tube immunofluorescence titre was the more marked. It is evident that the anti-germ tube immunofluorescence assay is more discriminatory for C. albicans infection than the conventional ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…However, after exhaustive reaction of anti-G with Y cells, the absorbed serum, which contained precipitin to component II, gave an IF reaction confined to the germ tubes of G cells. Immunofluorescence confined to the germ tubes was likewise observed with some human sera at high dilution (Ho et al, 1976). It seems that component II is probably localised on the germ tubes.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, after exhaustive reaction of anti-G with Y cells, the absorbed serum, which contained precipitin to component II, gave an IF reaction confined to the germ tubes of G cells. Immunofluorescence confined to the germ tubes was likewise observed with some human sera at high dilution (Ho et al, 1976). It seems that component II is probably localised on the germ tubes.…”
Section: Discussionmentioning
confidence: 71%
“…IF assays were performed as described by Ho et al (1976). Serially diluted sera were allowed to react with acetone-fixed smears of G cells or Y cells for one hour.…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Toutefois, il est intéressant de signaler un travail récent de Ho et al [24] Pour le diagnostic biologique de l'aspergillose, la standardisation de l'antigène est moins bonne: on utilise suivant les auteurs: soit des coupes- En particulier, l'hémagglutination passive est utilisable et présente un intérêt certain pour le diagnostic biologique des candidoses [29]. Selon la nature de l'antigène cytoplasmique, antigène somatique, complexes mannanes-protéine...), le seuil de spécificité de la réaction se situe entre le titre 1/80 et 1/320.…”
Section: Immunofluorescenceunclassified
“…This distinction is difficult to make by cultural examination, although the demonstration of mycelial forms in the specimen or biopsy material has been regarded as an important indication of infection (Winner, 1969). Recently, it has been suggested that the demonstration of serum antibody to mycelial rather than blastospore antigens, using a fluorescent antibody method, is a simpler and more sensitive way of detecting deep tissue infection (Ho et al, 1976). Heavy colonisation of the mouth, pharynx, gut, and urinary tract by the organism is now commonly seen in patients receiving broad-spectrum antibiotics (Seelig, 1966) and the progress of the colonisation requires careful monitoring if deep tissue infection or septicaemia are to be avoided.…”
mentioning
confidence: 99%